The Emerging Roles of Ferroptosis in Vascular Cognitive Impairment - Nao Yan (Frontiers in Neuroscience, 2019)
Vascular cognitive impairment (VCI) is a clinical syndrome that encompasses all forms of cognitive deficits caused by cerebrovascular disease, from mild cognitive impairment to dementia. Vascular dementia, the second most common type of dementia after Alzheimer’s disease (AD), accounts for approximately 20% of dementia patients. Ferroptosis is a recently defined iron-dependent form of cell death, which is distinct from apoptosis, necrosis, autophagy, and other forms of cell death. Emerging evidence suggests that ferroptosis has significant implications in neurological diseases such as stroke, traumatic brain injury, and AD. Additionally, ferroptosis inhibition has an obvious neuroprotective effect and ameliorates cognitive impairment in various animal models. Here, we summarize the underlying mechanisms of ferroptosis and review the close relationship between ferroptosis and VCI.